2015
DOI: 10.5935/1806-0013.20150057
|View full text |Cite
|
Sign up to set email alerts
|

Central neuropathic pain: implications on quality of life of spinal cord injury patients

Abstract: BACKGROUND AND OBJECTIVES: Pain is one consequence of spinal cord injury, added to micturition and intestinal disorders, changes in sexuality and reproduction, and social and family issues. Understanding pain and its interference with quality of life may help professionals assisting patients to find the most adequate way to control neuropathic pain. Investigators of the International Association for the Study of Pain have evaluated articles from 1975 to 2007 and have observed that the least studied subject was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…In terms of demographics, the only significant relationship identified in this study was between marital status and NP prevalence. Rita et al reported that pain intensity among married patients was higher than that among single patients with traumatic SCI [ 31 ]. In one study, a univariate analysis of a cohort of patients with traumatic SCI found that married patients reported more pain interference 2 years post-injury than single patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of demographics, the only significant relationship identified in this study was between marital status and NP prevalence. Rita et al reported that pain intensity among married patients was higher than that among single patients with traumatic SCI [ 31 ]. In one study, a univariate analysis of a cohort of patients with traumatic SCI found that married patients reported more pain interference 2 years post-injury than single patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual functions are a very important factor in the QOL; recovery of these activities is the highest priority in patients with paraplegia and is in second place of priority in the tetraplegic patients after recovery of hand function [31,32]. Numerous studies have shown that sexual life is one of lower-graded components of the WHOQOL-BREF scale [33][34][35], with lower scores compared to the general population [36]. Anderson et al [37] attempted to answer the question of whether improvement of sexual function might significantly improve the QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Com relação ao domínio dor houve melhora nos escores. A dor pode exercer um papel bastante negativo, não só no desempenho da sexualidade, como no desempenho ocupacional geral (Aquarone, Faro & Nogueira, 2015). A atividade física, como o fortalecimento, libera endorfina, potente analgésico endógeno que reduz a dor e o estresse e, além disso, aumenta a produção de serotonina.…”
Section: Qualidade De Vidaunclassified
“…Em condições normais, as atividades sexuais seguem um processo natural, controlado pelo Sistema Nervoso Central que envia as mensagens à medula espinhal, provocando reações no sistema autônomo (como a ereção) (Aquarone, Faro & Nogueira, 2015). Para que essas reações aconteçam, os neurotransmissores dopaminérgicos são disparados na fenda sináptica, despolarizando a membrana, sendo considerado um potencial de ação excitatório do sistema nervoso.…”
Section: Introductionunclassified